2014
DOI: 10.1155/2014/480149
|View full text |Cite
|
Sign up to set email alerts
|

An Environmentally Friendly Process for the Preparation of UHMWPE As-Spun Fibres

Abstract: The extrusion of ultra high molecular weight polyethylene (UHMWPE) fibres cannot be achieved by conventional extrusion processes due to its very high melt viscosity. To overcome this limitation, UHMWPE is first dissolved in a petrochemical to form a gel before extrusion. The petrochemicals used to dissolve the polymer then need to be removed using other chemicals making the process unfriendly to the environment. This article is focused on finding an environmentally friendly, natural solution to replace these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…2,6-Di-tetra-butyl-4-methylphenol antioxidant was also supplied by Sigma-Aldrich. Samples were prepared as reported previously by the author [11]. Tensile tests were carried out on Instron 3345.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6-Di-tetra-butyl-4-methylphenol antioxidant was also supplied by Sigma-Aldrich. Samples were prepared as reported previously by the author [11]. Tensile tests were carried out on Instron 3345.…”
Section: Methodsmentioning
confidence: 99%
“…In the second stage gel like fibres are treated with extraction solvent to remove petrochemical solvent. In present work gel spinning was carried out utilizing terpene based gel spinning process developed by author [11] instead of petrochemicals used in conventional gel spinning of UHMWPE. The schematic diagram of newly developed process is shown in figure 1.…”
Section: Rezumat -Abstractmentioning
confidence: 99%
“…[56] Recovery of such solvents in large volume can present potentially serious health concerns. [57] Recently, however, Schaller et al reported gel-spinning of UHMWPE using olive oil, peanut oil, stearic acid, and lauric acid as solvents, which yielded enhanced productivity and properties, as shown in Figure 3. [58] These solvents were extracted using isopropanol and diethyl ether.…”
Section: Current State and Challenges Of High Performance Fibermentioning
confidence: 99%
“…But compared with other preparation methods, the gel‐spinning‐hot‐drawing method has many merits, such as excellent properties of prepared fibers, easy control of spinning process and so on. At present, the most mature industrial‐spun UHMWPE fibers have been widely industrialized only gel‐spinning‐hot‐drawing method 4,16 …”
Section: Introductionmentioning
confidence: 99%
“…At present, the most mature industrial-spun UHMWPE fibers have been widely industrialized only gel-spinning-hot-drawing method. 4,16 The key processes of UHMWPE fibers production by gel-spinning-hot-drawing include UHMWPE solution preparation, gel-spinning forming, solvent removal of gel fibers and ultra-hot drawing of dry gel fibers. 17,18 The first priority of gel-spinning method is to prepare a homogeneous UHMWPE spinning solution.…”
Section: Introductionmentioning
confidence: 99%